Tip-sample interactions on graphite studied using the wavelet transform - Malegori, Giovanna; Ferrini, Gabriele (Beilstein Journal of Nanotechnology, 2010)
Wavelet transform analysis is applied to a thermally excited cantilever to get insights into fundamental thermodynamical properties of its motion. The shortcomings of the widely used Fourier analysis are briefly discussed to put into perspective the wavelet transform analysis, used to describe the temporal evolution of the spectral content of the thermal oscillations of a cantilever with an interacting tip. This analysis allows to retrieve the force gradients, the forces and the Hamaker constant in a measurement time of less than 40 ms.
Keywords: AFM; force; graphite; thermal excitation; wavelet transforms

Noncontact Atomic Force Microscopy - Morita, S.; Wiesendanger, R.; Meyer, E. (Springer, 2002)

(untitled) - Garcia, R.; Pérez, R. (Surf. Sci. Rep., 2002)

(untitled) - Butt, H. J.; Cappella, B.; Kappl, M. (Surf. Sci. Rep., 2005)

(untitled) - Sugimoto, Y.; Pou, P.; Abe, M.; Jelinek, P.; Pérez, R.; Morita, S.; Custance, O. (Nature, 2007)

(untitled) - Gross, L.; Mohn, F.; Moll, N.; Liljeroth, P.; Meyer, G. (Science, 2009)

(untitled) - García, R.; Magerle, R.; Pérez, R. (Nat. Mater., 2007)

(untitled) - Cleveland, J. P.; Schäffer, T. E.; Hansma, P. K. (Phys. Rev. B, 1995)

(untitled) - Roters, A.; Johannsmann, D. (J. Phys.: Condens. Matter, 1996)

An Introduction to Wavelets - Chui, C. K. (Academic Press)

A Wavelet Tour of Signal Processing - Mallat, S. G. (Academic Press, 1999)

(untitled) - Carmichael, M.; Vidu, R.; Maksumov, A.; Palazoglu, A.; Stroeve, P. (Langmuir, 2004)

(untitled) - Gackenheimer, C.; Cayon, L.; Reifenberger, R. (Ultramicroscopy, 2009)

(untitled) - Siria, A.; Drezet, A.; Marchi, F.; Comin, F.; Huant, S.; Chevrier, J. (Phys. Rev. Lett., 2009)

(untitled) - Deng, Y.; Wang, C.; Chai, L.; Zhang, Z. (Appl. Phys. B: Lasers Opt., 2005)

(untitled) - Albrecht, T. R.; Grütter, P.; Horne, D.; Rugar, D. (J. Appl. Phys., 1991)

Laser Spectroscopy - Demtröder, W. (Springer, 2003)

(untitled) - Sader, J. E.; Chon, J. W. M.; Mulvaney, P. (Rev. Sci. Instrum., 1999)

(untitled) - Butt, H. J.; Jaschke, M. (Nanotechnology, 1995)

(untitled) - Lévy, R.; Maaloum, M. (Nanotechnology, 2002)

(untitled) - Hutter, J. L. (Langmuir, 2005)